MEC684: Design of Mechatronic Systems / College of Engineering - UiTM, College of Engineering (2023)
The course aims to introduce the student with the systems engineering framework and related design methodologies for hardware and software integration of Mechatronic systems. This course covers the design process of mechatronic systems, actuator types, transducer and measurement systems, signal conditioning and control system, and case studies of various mechatronics systems.